Clinical study of the marginal microfiltration in restorations with amalgam applying sealant cavitario - Lahoud Salem, Víctor (2006)
The present study to evaluate the clinical evaluation, marginal leakage of 30 amalgams restorations with sealers cavity and 30 amalgams restorations not sealers cavity. After of 12 months observation in amalgams restorations with sealers cavity 100% success in marginal leakage and not presents of secondary caries, not to have presents clinical cases of sensitivity post-operative and pulp inflammation.